2022
DOI: 10.1186/s12935-022-02834-1
|View full text |Cite
|
Sign up to set email alerts
|

Cell senescence-associated genes predict the malignant characteristics of glioblastoma

Abstract: Background Glioblastoma (GBM) is the most malignant, aggressive and recurrent primary brain tumor. Cell senescence can cause irreversible cessation of cell division in normally proliferating cells. According to studies, senescence is a primary anti-tumor mechanism that may be seen in a variety of tumor types. It halts the growth and spread of tumors. Tumor suppressive functions held by cellular senescence provide new directions and pathways to promote cancer therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Wang et al (Wang et al, 2022) used the senescence-related gene set to define a cellular senescence score in pancancer and demonstrated that this score can represent the degree of immune activation in the tumor microenvironment and can identify groups with better prognosis. In specific cancers, researchers have also constructed classification models and prognostic prediction models based on senescence gene sets, including clear cell renal cell carcinoma (Lu et al, 2022), hepatocellular carcinoma (Luo et al, 2022), glioblastoma (Tan et al, 2022), etc., and explored the relationship between senescencerelated genes and clinical characteristics, tumor microenvironment, immunotherapy, etc. These studies demonstrate the importance of senescence genes in cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (Wang et al, 2022) used the senescence-related gene set to define a cellular senescence score in pancancer and demonstrated that this score can represent the degree of immune activation in the tumor microenvironment and can identify groups with better prognosis. In specific cancers, researchers have also constructed classification models and prognostic prediction models based on senescence gene sets, including clear cell renal cell carcinoma (Lu et al, 2022), hepatocellular carcinoma (Luo et al, 2022), glioblastoma (Tan et al, 2022), etc., and explored the relationship between senescencerelated genes and clinical characteristics, tumor microenvironment, immunotherapy, etc. These studies demonstrate the importance of senescence genes in cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Many prognostic models have previously been reported in GBM. For example, a study reported a prognostic model constructed by 11 cell senescence-associated genes in GBM ( 16 ). In addition, it was also found that the model constructed by m6A-Related lncRNA could predict the prognosis of GBM patients ( 17 ).…”
Section: Introductionmentioning
confidence: 99%